Islamic Microfinance as a Productive Investment Instrument In Empowering MSMEs - Dian Meinarni (FEBI IAIN Langsa, 2026)
Islamic microfinance has strategic potential as a productive investment instrument in empowering Micro, Small, and Medium Enterprises (MSMEs), but a comprehensive synthesis of this position is still absent from the literature. This research aims to map research trends, synthesize models and mechanisms that have proven to be effective, and formulate a future research agenda in the field of Islamic microfinance and MSME empowerment. The method used is Systematic Literature Review (SLR) with the PRISMA 2020 protocol, covering a systematic search on four databases (Scopus, Web of Science, Google Scholar, DOAJ) for the period 2015–2025. Of the 847 articles identified, 65 articles met the inclusion criteria and were synthesized using bibliometric analysis (VOSviewer) and thematic synthesis (framework analysis). The results show a significant increase in publication productivity since 2019, with Indonesia and Malaysia as the dominant contributors. Four Islamic microfinance models were identified as effective: the Sharia Graduation Model, Integrated Zakat-Microfinance, Productive Waqf, and Sharia Fintech, with the first two models having the strongest evidence base. Five priority research agendas were formulated, including standardization of productive investment indicators, longitudinal studies, integration of sharia fintech, synergy of zakat-state budget, and comparative studies across OIC countries. This research contributes by introducing a new framing of Islamic microfinance as a productive investment instrument, filling a conceptual gap that has not been answered in the Islamic economic literature